HUBUNGAN ASUPAN SERAT, ASUPAN ASAM FOLAT, DAN ASUPAN KALSIUM DENGAN KEJADIAN HIPERTENSI PADA PRA LANSIA DI KELURAHAN PELA MAMPANG - Nabilah Alianah Apriliani (2020)
In Indonesia, the prevalence of hypertension increased. South Jakarta, the prevalence of hypertension also increased so it needs to be considered. Food consumption is a risk factor for hypertension. Low fiber intake is known to increase blood pressure because fiber can bind bile acids which are the end products of cholesterol. Folic acid is also associated with hypertension through its role in homocysteine metabolism. Hypertension is also influenced by low calcium intake which causes disruption of calcium metabolism which triggers contraction of muscle cells. This study aimed to determine the relationship of fiber intake, folic acid intake, and calcium intake with the incidence of hypertension among pre elderly in Pela Mampang. The design of this study was cross sectional with 50 subjects selected using accidental sampling method. Data on fiber, folic acid, and calcium intake were collected based on interviews using SQ-FFQ over the past month and blood pressure measurements using a digital sphygmomanometer. Data analysis using chi-square test. The results of this study were respondents who experienced hypertension by 50% and no hypertension by 50% and there was no relationship between fiber intake (p = 0.247), folic acid intake (p = 0.520), and calcium intake (p = 0.349) with the incidence hypertension among pre elderly. So, prevention need to be done, likely lifestyle modification and socialization to the community related to hypertension so that the incidence of hypertension can be controlled.